RENAL PREZERVASYONDA HİPOTERMİ SÜRESİNE BAĞLI ALLOGRAFTTA GÖRÜLEN ULTRASTRÜKTÜREL DEĞİŞİKLİKLER: İKİ AYRI SOLÜSYONUN KARŞILAŞTIRILMASI - MEHMEDOĞLU, Akif; Seçkin, İsmail and ÖNDER, Ali Ulvi and Sarıyar, Muzaffer (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Euro-Collins (UC) and University of Wisconsin (UW) solutions are the most widely used solutions as the storage media of different organs prior to the transplantation. This experimental study was performed to investigate the renal ultrastructural changes caused by hypothermia during renal allograft preservation with UW and EC solutions at 12, 24 and 48 hours. Result.- We observed minimal degeneration in the kidney structure following EC and UW perfusion at 12 hr preservation. The kidneys in UW group were better preserved when compared with EC group following more than 24 hr of preservation. Mitochondria of renal tubule cells podocytes and endothelial cells were also showed minimal degeneration and there were no erythrocyte aggregation and adhesion to capillary endothelium in UW group in EC group vacoolization and mitochondrial degeneration of these cells were prominent and erythrocyte aggregation and adhesion were seen. After ≥ 48 hr of preservation erythrocyte aggregation and adhesion to capillary endothelium were seen in UW group. Degeneration of renal tubule cells, endothelium and podocytes were increased in both groups. Conclusion.- We have observed the ultrastructural changes of kidneys following EC and UW perfusion of 12 hr, 24 hr, 48 hr for renal preservation. We have concluded that UW solution was seen to have better protective effect on kidney structure in same time period and erythrocytes aggregation and adhesion to endothelium appeared later periods of time (48 hr) when compared to EC solution.